Globalz Car Wash / Eka Pusmawati Abd Wasir ... [et al.] - Abd Wasir, Eka Pusmawati; Kaharuddin, Nurhamidah; Pg Othman, Dk Nurul Atiqah; Anam, Rojita (2011)
Car wash is a good services business that suitable to run on for the people who is started to try involved in business services area. The most important for running a business car was is a suitable location with basic equipment and a few workers to the job. As started in the news Bernama that car wash is profitable business when student UM raise their fund for "BAKTI SISWA SARAWAK 2000" project.This is the second time their do the project. At the fist time the projects prove that this project is success. The car wash also gives benefits to our environment. The chemical oxidation of car wash industry as effort to decreases water pollution. Wastewater from car washing station contain a number of impurities such as sand and dust ,free oil .grease, oil/emulsion carbon .asphalt, salt, surfactant and organic matter, which is discharged directly into municipal sewage treatment plant.